Shear properties of jointed dual-pylon of the cable-stayed bridge with separated unequal-width decks under asymmetric load - Chao Luo; Jingzhou Xin; Jiafeng Yang; Yan Jiang; Lei Huang; Jianting Zhou (Advances in Bridge Engineering)
Abstract The significant load disparity between the two decks of a cable-stayed bridge with separated unequal-width decks results in complex asymmetric static effects in the jointed dual-pylon. To investigate the structural behaviour and reliability of the jointed dual-pylon under asymmetric loads, a 1:30 scaled model test and numerical simulation were conducted based on the world's first road-railway same-level cable-stayed bridge with jointed pylons. The test results indicate when the unbalanced horizontal force of the jointed dual-pylon structure reaches its maximum during the service phase, the stress at the dual-pylon connectivity node remains relatively low, indicating good shear resistance of the dual-pylon connectivity node. Structural failure occurs when the load reaches 1.82 times the maximum shear stress at the tower column merging section, and the railway beam will experience severe cracking and stiffness degradation, ultimately leading to loss of bearing capacity. The calculation results further reveal that under the combined action of dead load, full-span moving load, and lateral wind load, the minimum calculated nonlinear stability coefficient of the dual-pylon connectivity node is 1.65. Moving load and longitudinal wind load have minimal impact on the nonlinear stability coefficient, and the dead load and lateral wind load primarily govern the failure of the dual-pylon connectivity node.